Early prognostic value of nocturnal blood pressure: a single-centre experience. Issue 3 (June 2019) - Fabbian, Fabio; Tonelli, Laura; De Giorgi, Alfredo; Cappadona, Rosaria; Pasin, Mauro; Manfredini, Roberto
Abstract : Ambulatory blood pressure monitoring (ABPM) is now considered by current guidelines to be a reliable method of measurement for the diagnosis and assessment of hypertension. The aim of this study was to relate the short-term outcomes, comorbidity and ABPM findings determined from evaluating an everyday clinical cohort of hypertensive patients. A prospective study was carried out that included hypertensive patients who had undergone 24-h ABPM from January 2016 to November 2017. The following parameters were recorded in the database: age, sex, current antihypertensive treatment and documented history of comorbidities. New episodes of myocardial infarction and stroke requiring hospitalization during follow-up obtained from electronic medical records were considered to be major adverse cardiovascular events (MACE) and were our main outcome measures. To estimate the risk of MACE, a Cox multivariate analysis was carried out. We analysed 1521 ABPM values and recorded 33 MACE during a follow-up of 518±120 days; 15 patients suffered a myocardial infarction and 18 patients had a stroke. The mean age of the patients was 59.9±14.2 years, and 49.4% were men. Night-time systolic blood pressure (BP), mean BP and pulse pressure were higher in patients who suffered a MACE. Age [hazard ratio (HR): 1.031, 95% confidence interval (CI): 1.002–1.060; P =0.036], night-time BP (HR: 1.018, 95% CI: 1.001–1.037; P =0.044) and diabetes mellitus (HR: 2.393, 95% CI: 1.053–5.436; P =0.037) were associated independently with MACE. We conclude that night-time BP is an important parameter to evaluate in aged patients with diabetes as a predictor of MACE.